High cost burden and health consequences of antibiotic resistance: the price to pay - Sujith J Chandy; Girish S Naik; Veeraraghavan Balaji; Visalakshi Jeyaseelan; Kurien Thomas; Cecilia Stalsby Lundborg (Journal of Infection in Developing Countries)
Introduction: Rising antibiotic resistance may negatively affect the health and cost of care for patients. This study aimed to determine the impact of antibiotic resistance on costs and health consequences for patients. Methodology:  A one-year observational study was conducted at Christian Medical College, Vellore, a tertiary care hospital, on patients admitted into medical wards with a preliminary diagnosis of suspected sepsis. Patients with confirmed bacteremia were analysed in two groups – resistant and susceptible – based on susceptibility of causative bacteria to the empiric antibiotics administered. Clinical data and details about costs incurred were collected from hospital records. Costs and health consequences were compared using Mann-Whitney U test and Fisher’s exact test. For median difference in costs, 95% bootstrap confidence interval was determined. Results: Overall, 220 patients were included. The median difference between resistant and susceptible groups in overall costs, antibiotic costs, and pharmacy costs was rupees (INR)/USD 41,993/700 (p = 0.001), 8,315/139 (p < 0.001) and 21,492/358 (p < 0.001), respectively. Health consequences such as intensive care admissions, complications, mortality, and length of stay were significantly higher in the resistant group as compared to susceptible group: 44% vs. 21% (p < 0.001), 56% vs. 37% (p = 0.006), 12% vs. 2% (p = 0.011), and 14 vs. 11 days (p = 0·027), respectively. Conclusions: Antibiotic resistance has a significant impact on cost and health consequences. These findings provide a key message for policymakers and other stakeholders to initiate feasible strategies to tackle resistance and reduce the burden.